2010
DOI: 10.1093/fampra/cmq009
|View full text |Cite
|
Sign up to set email alerts
|

A pilot quality improvement intervention in patients with diabetes and hypertension in primary care settings of Cyprus

Abstract: A pilot multifaceted quality improvement intervention programme for patients with diabetes and HTN implemented in primary care settings in Cyprus showed promising results. Future studies need to involve a broader number of practices and patient populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 30 publications
2
19
0
Order By: Relevance
“…We found that there were significant improvements in the absolute change in the proportion of PCPs' adherence to T2DM CPG in the intervention group with regard to the recording of BMI, performing foot examination, performing funduscopy/fundus photography, monitoring renal profile, measuring urine protein, and giving lifestyle modification and self-management advice. These findings were similar to a randomized controlled trial involving 504 patients (278 patients in the intervention practices and 226 patients in the control practices) which showed that the mean results of three annual performance measures (urine protein testing, funduscopy, and foot examination) had improved at 18-month follow-up in the intervention group as compared to the control group [32]. Another study of 208 patients showed that 85.5% had more than twice HbA1c test done in a year, 93.6% had lipid profiles test, and 100% had foot examinations following a multifaceted intervention [33].…”
Section: Discussionsupporting
confidence: 81%
“…We found that there were significant improvements in the absolute change in the proportion of PCPs' adherence to T2DM CPG in the intervention group with regard to the recording of BMI, performing foot examination, performing funduscopy/fundus photography, monitoring renal profile, measuring urine protein, and giving lifestyle modification and self-management advice. These findings were similar to a randomized controlled trial involving 504 patients (278 patients in the intervention practices and 226 patients in the control practices) which showed that the mean results of three annual performance measures (urine protein testing, funduscopy, and foot examination) had improved at 18-month follow-up in the intervention group as compared to the control group [32]. Another study of 208 patients showed that 85.5% had more than twice HbA1c test done in a year, 93.6% had lipid profiles test, and 100% had foot examinations following a multifaceted intervention [33].…”
Section: Discussionsupporting
confidence: 81%
“…Multi-faceted interventions, grounded on several theories and models, have been developed in Cyprus to provide better quality of care for hypertensive patients in primary care settings [ 76 ]. Such approaches, like one incorporating both an electronic medical record system and guidelines for managing clinical diseases, showed positive outcomes for hypertensive patients on many measures including blood pressure, total cholesterol and patient satisfaction [ 77 ]. Whilst a majority of physicians in Cyprus are aware of and adhere to guidelines on managing hypertension, there is great scope to improve not only their awareness of specific European scientific guidelines (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…There is already evidence that Cypriot patients, their carers and health care professionals are prepared to welcome new diabetes management models able to promote patient autonomy and self-management, and closer relationship between patient and health care professional. [13][14] This study aimed at understanding patients' preferences when choosing health care services for their diabetes care, and how they value SDM, as a process in which healthcare professionals and patients work together to select tests, treatments, management, or support packages, based on clinical evidence and patients' informed preferences. Results allowed to estimate the components of SDM that people value, their relative importance; but also the potential participation rates to SDM programmes.…”
Section: Introductionmentioning
confidence: 99%